Students’ personal factors as a determinant of entrepreneurial intention - Azman Ismail; Hidayati Ernida Hassan Azahari (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2017)
This study examines the relationship between students’ personal factors (i.e., personal attitude and perceived behavioural control) and entrepreneurial intention by using 130 survey questionnaires gathered from students in an economic and business faculty in Malaysian public research university. The outcomes of SmartPLS analysis revealed two main findings: first, personal attitude was significantly correlated with entrepreneurial intention. Second, perceived behavioural control was significantly correlated with entrepreneurial intention. This result demonstrates the personal attitude and perceived behavioural control act as important determinants of students’ entrepreneurial intention in the studied organization.